What Women Want (Their Men to Do): Housework and Satisfaction in Australian Households - Gigi Foster; Leslie S. Stratton (Institute of Labor Economics (IZA), 2017)
The time allocated to household chores is substantial, with the burden falling disproportionately upon women. Further, social norms about how much work men and women should contribute in the home are likely to influence couples' housework allocation decisions and evaluations of their lot. Using Australian data, we employ a two-stage estimation procedure to examine how deviations from housework norms relate to couples' satisfaction. In stage one, we model housework time to identify predicted (i.e., socially expected) and residual components. In support of this bifurcation, the residual housework time measures are strongly related to each partner's perceived fairness of the division of household tasks. In stage two, we predict satisfaction based on predicted and residual housework time. We find that women's satisfaction, but not men's, is robustly affected by their partners' residual housework time. When he exceeds housework norms, she is happier with housework allocations, but less happy in broader dimensions.
Keywords: D13; I31; Z13; 330; social norms; satisfaction; housework